Avaliando a qualidade dos serviços de distribuiç\~ao de energia elétrica no Brasil - Mário Jorge Cardoso De Mendonça; Amaro Olimpio Pereira Júnior; Jose Francisco Moreira Pessanha; Luis Alberto Toscano Medrano; Marlon Max H. Bellido (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
Among the aspects related to the quality of electric power supply, continuity stands out, evaluated based on the DEC and FEC indicators that express, respectively, the duration and frequency of supply interruptions. Regarding the continuity of supply, this study aims to present an alternative approach to the current methodology implemented by ANEEL for evaluating the performance of distributors in the Brazilian Electric System. For this purpose, a stochastic frontier analysis is proposed for benchmarking the continuity indicators of electric power distributors. The proposed model estimated based on bayesian inference is still capable of contemplating the temporal dynamics of efficiency. The consideration of this point is fundamental, because the studies done to evaluate the efficiency of the electric sector have neglected the fact that part of the increase in efficiency of a utility comes from the gain of scale due to the expansion of the market, a process that happens over time. Consideration of the dynamic aspect of efficiency is also of great importance for tariff revision. It was observed that actions of the utilities managed to keep the FEC below the regulatory goal, while the DEC exceeded the limit during 2009-2019. In order to assist the regulator in calibrating local continuity targets, it was also proposed to apply the efficiency indexes to define annual global targets for the continuity indicators. The results showed that the limits defined by our methodology are compatible with the limits defined by ANEEL and are perfectly feasible to be exceeded by the utilities.
Keywords: D24; L60; L94; O13; 330; utilities; continuity of supply; SAIDI; SAIFI; efficiency; stochastic frontier; bayesian inference